1988
DOI: 10.1079/bjn19880108
|View full text |Cite
|
Sign up to set email alerts
|

Time-course effects of protein malnutrition on hepatic fatty acids Δ6 and Δ5 desaturation in the growing rat

Abstract: 1. In growing rats, the time-course effects of giving a normal-protein diet (200 g casein/kg; NP) for 52 d, a lowprotein diet (20 g casein/kg; LP) for 52 d and a LP diet for 26 d followed by balanced refeeding (200 g casein/ kg; BR) for 26d, on the fatty acid composition of liver total lipids and microsomal phospholipids were investigated together with 66-and A5-microsomal desaturase activities.2. The oleic acid content (mg/g tissue) of liver total lipids increased progressively with the LP diet, while linolei… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
18
0

Year Published

1989
1989
2010
2010

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 36 publications
(18 citation statements)
references
References 36 publications
0
18
0
Order By: Relevance
“…This may at first seem surprising given the difference in measured D5 desaturase activity. Apparent discrepancies between desaturase activities and phospholipid composition have also been reported previously [14,15]. This is not unexpected as membrane incorporated arachidonic acid could arise from two sources.…”
Section: Discussionmentioning
confidence: 69%
See 1 more Smart Citation
“…This may at first seem surprising given the difference in measured D5 desaturase activity. Apparent discrepancies between desaturase activities and phospholipid composition have also been reported previously [14,15]. This is not unexpected as membrane incorporated arachidonic acid could arise from two sources.…”
Section: Discussionmentioning
confidence: 69%
“…The activity of D6 and D5 desaturases were assayed according to a published method [9] using [1][2][3][4][5][6][7][8][9][10][11][12][13][14] C] labelled linoleic acid (18:2n-6) and eicosatrienoic acid (20:3n-6) fatty acids as their respective substrates. After reaction, fatty acids were saponified, transmethylated and spotted onto 10 % silver nitrate-impregnated silica gel thin-layer chromatography plates (Merck, Darmstadt, Germany) with known standards.…”
Section: Methodsmentioning
confidence: 99%
“…The inherent difficulty of measuring desaturase activities directly has led to the use of fatty acid product/substrate ratios as surrogate estimates of desaturase activities. This approach is supported to some degree by results from animal studies [21][22][23][24], but compelling evidence is lacking. Importantly, the absence of human data on the validity of these relationships is of concern, since mice, in contrast to humans, express various isoforms of SCD with different affinities for the precursor fatty acids [4].…”
Section: Discussionmentioning
confidence: 99%
“…Numerous studies have supported the importance of zinc in the metabolism of EFAs, as reviewed by Cunnane et al 35,36 Finally, decreased protein (more specifically, deficiencies in certain amino acids) may alter EFA metabolism. 37 PEM is frequently associated with EFA deficiency, and it has been suggested that many of the clinical symptoms-including skin changes-seen in these malnourished individuals may be at least partially attributed to EFA deficiency. 38 In conclusion, the dermatitis seen in infants with CF is likely multifactorial, with deficiencies in zinc, EFAs, and protein contributing to its development.…”
Section: Commentmentioning
confidence: 99%